The "cabrei" of the Archivio di Stato di Bologna: a complex reading - Elena Gonnelli (JLIS.it, 2023)
The term cabreo has been given different meanings over the years: what was originally defined as a legal and then economic instrument, has increasingly acquired an aesthetic connotation that made it more like a piece of art. Starting from its definitions, we will try to show how, at the heart of the cabreo representation, there is a complex system of relationships: the patronage, the drafters, the subscribers, and the apparatuses are all elements that add information to the picture. Taking a few significant examples from the documentary heritage of the Archivio di Stato di Bologna, we will try to show how the examination of the graphic artefacts allows us to reconstruct the field of action of public institutions, private individuals and religious corporations, if analysed in its reference framework.